Inactivation of NUPR1 promotes cell death by coupling ER-stress responses with necrosis. Issue 1 (December 2018) - Santofimia-Castaño, Patricia; Lan, Wenjun; Bintz, Jennifer; Gayet, Odile; Carrier, Alice; Lomberk, Gwen; Neira, José; González, Antonio; Urrutia, Raul; Soubeyran, Philippe; Iovanna, Juan
Abstract It was already described that genetic inhibition of NUPR1 induces tumor growth arrest. In this paper we studied the metabolism changes after NUPR1 downregulation in pancreatic cancer cells, which results in a significant decrease of OXPHOS activity with a concomitant lower ATP production which precedes the necrotic cell death. We demonstrated that NUPR1 downregulation induces a mitochondrial failure with a loss of the mitochondrial membrane potential, a strong increase in ROS production and a concomitant relocalization of mitochondria to the vicinity of the endoplasmic reticulum (ER). In addition, the transcriptomic analysis of NUPR1-deficient cells shows a decrease in the expression of some ER stress response-associated genes. Indeed, in ER stressors-treated cells with thapsigargin, brefeldin A or tunicamycin, a greater increase in necrosis and decrease of ATP content was observed in NUPR1-defficent cells. Finally, in vivo experiments, using acute pancreatitis which induces ER stress as well as NUPR1 activation, we observed that NUPR1 expression protects acinar cells from necrosis in mice. Importantly, we also report that the cell death observed after knocking-down NUPR1 expression is completely reversed by incubation with Necrostatin-1, but not by inhibiting caspase activity with Z-VAD-FMK. Altogether, these data enable us to describe a model in which inactivation of NUPR1 in pancreatic cancer cells results in an ER stress that induces a mitochondrial malfunction, a deficient ATP production and, as consequence, the cell death mediated by a programmed necrosis.